2022
DOI: 10.1108/imefm-01-2022-0041
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 and informational efficiency in Asian emerging markets: a comparative study of conventional and Shariah-compliant stocks

Abstract: Purpose This study aims to provide a comparative insight into the level of informational efficiency and irregularities of Shariah-compliant stocks and conventional stocks in three emerging markets, namely, China, Malaysia and Pakistan. The empirical evidence is provided for pre-crisis and crisis periods caused by the Covid-19 pandemic. Design/methodology/approach Informational efficiency is measured using the variance ratio (VR) Test developed by Kim (2006). The Approximate Entropy (ApEn) Metrics is used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Impact of the quarantine regime on the level of investments according to the sector. References (Adnan and Hasan 2021;Ali et al 2022;Asteriou et al 2023;Clark et al 2021;González and Gallizo 2021;Hasnaoui et al 2021;Huynh et al 2021;Kurien ė 2022;Liedtke 2021;Liu et al 2022;Lutfi et al 2022;Nguyen and Vu 2021;Nikolajenko et al 2021;Pileckait ė and Subačien ė 2023;Pourmansouri et al 2022;Rahman et al 2022;Ramachandran et al 2021;Raza et al 2022;Senkus et al 2022;Shabir et al 2023;Simoens and Vander Vennet 2022;S ūdži ūt ė and Jakubavičius 2022;Toth et al 2022;Wulandari et al 2022;Zheng and Zhang 2020;Žinyt ė and Jurkonien ė 2023) are cited in the supplementary materials.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Impact of the quarantine regime on the level of investments according to the sector. References (Adnan and Hasan 2021;Ali et al 2022;Asteriou et al 2023;Clark et al 2021;González and Gallizo 2021;Hasnaoui et al 2021;Huynh et al 2021;Kurien ė 2022;Liedtke 2021;Liu et al 2022;Lutfi et al 2022;Nguyen and Vu 2021;Nikolajenko et al 2021;Pileckait ė and Subačien ė 2023;Pourmansouri et al 2022;Rahman et al 2022;Ramachandran et al 2021;Raza et al 2022;Senkus et al 2022;Shabir et al 2023;Simoens and Vander Vennet 2022;S ūdži ūt ė and Jakubavičius 2022;Toth et al 2022;Wulandari et al 2022;Zheng and Zhang 2020;Žinyt ė and Jurkonien ė 2023) are cited in the supplementary materials.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…A recent study by Boudt et al (2019a) compared the financial performance of CEPs and SCEPs in macrofinancial regimes and found that both these portfolios have different exposure to different regimes. Similarly, studies conducted by Hassan et al (2021) and Raza et al (2022) search for the safe haven properties of these indices in the Global Financial Crisis and Global Pandemic Crisis caused by To the best of our knowledge, Shugaa and Masih (2014) and Ahmed (2018) are the only studies on the effect of political risk on the performance of internationally diversified SCEPs. The former focuses on the effect of spring uprisings on the volatility of SCEPs and CEPs in the MENA region, while the latter aims at the differential impact of political risk on both groups of portfolios.…”
Section: Introduction Does Political Risk Affect Portfolio Returns?mentioning
confidence: 99%
“…A recent study by Boudt et al (2019a) compared the financial performance of CEPs and SCEPs in macro-financial regimes and found that both these portfolios have different exposure to different regimes. Similarly, studies conducted by Hassan et al (2021) and Raza et al (2022) search for the safe haven properties of these indices in the Global Financial Crisis and Global Pandemic Crisis caused by Covid-19.…”
Section: Introductionmentioning
confidence: 99%
“…In efficient markets predicting stock prices using merely historical data is a cumbersome task. The EMH is a well-established concept and is widely discussed by academic literature, and its applications are evaluated globally by several studies in different time spans (see, e.g., Kim and Shamsuddin 2008;Lee 2012;Raza et al 2022). The term market efficiency is perceived in different contexts.…”
Section: Introduction Of the Studymentioning
confidence: 99%
“…The term market efficiency is perceived in different contexts. However, this study refers to the informational efficiency of the stock market, which is concerned with the degree of information reflected in stock prices (Raza et al 2022).…”
Section: Introduction Of the Studymentioning
confidence: 99%